2019
DOI: 10.3389/fnagi.2019.00112
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Oligodendrocytes in Tau Seeding and Spreading in Tauopathies

Abstract: Introduction: Human tau seeding and spreading occur following intracerebral inoculation into different gray matter regions of brain homogenates obtained from tauopathies in transgenic mice expressing wild or mutant tau, and in wild-type (WT) mice. However, little is known about tau propagation following inoculation in the white matter. Objectives: The present study is geared to learning about the patterns of tau seeding and cells involved following unilateral inoculation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 76 publications
(115 reference statements)
15
77
0
Order By: Relevance
“…Our previous studies have shown tau seeding and spreading following inoculation of sarkosyl-insoluble fractions from AD, primary age-related tauopathy (PART), aging-related tau astrogliopathy (ARTAG), progressive supranuclear palsy (PSP), Pick’s disease (PiD), frontotemporal lobar degeneration linked to MAPT P301L mutation, and sporadic and familial globular glial tauopathy (GGT) into the hippocampus and corpus callosum of WT mice ( Ferrer et al, 2018 , 2019 , 2020a , b ). The present study is focused on the capacity for and characteristics of seeding and propagation of phospho-tau from homogenates of “pure” (not associated with AD or other tauopathies) AGD cases in the hippocampus of WT mice.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown tau seeding and spreading following inoculation of sarkosyl-insoluble fractions from AD, primary age-related tauopathy (PART), aging-related tau astrogliopathy (ARTAG), progressive supranuclear palsy (PSP), Pick’s disease (PiD), frontotemporal lobar degeneration linked to MAPT P301L mutation, and sporadic and familial globular glial tauopathy (GGT) into the hippocampus and corpus callosum of WT mice ( Ferrer et al, 2018 , 2019 , 2020a , b ). The present study is focused on the capacity for and characteristics of seeding and propagation of phospho-tau from homogenates of “pure” (not associated with AD or other tauopathies) AGD cases in the hippocampus of WT mice.…”
Section: Introductionmentioning
confidence: 99%
“…However, no GAIs or GOIs, but only coiled bodies, are regularly seen in WT mice inoculated with sarkosyl-insoluble fractions of GGT linked to MAPT P301T mutation, sGGT, and GGT linked to MAPT K317M mutation in our study. The exception of a few bizarre oligodendroglial inclusions following inoculation of homogenates from MAPT K317M samples does not detract from the general concept that coiled bodies are the characteristic oligodendroglial phospho-tau inclusions in WT mice inoculated with homogenates from GGT and other tauopathies [36,37,41]. This suggests that host tau is crucial to recapitulate typical inclusions in human diseases.…”
Section: Seeding and Spreading Of Ggt Tau Following Intra-cerebral Inmentioning
confidence: 87%
“…Moreover, although GAIs and GOIs are typical of GGT, nothing is known about the functional alterations linked to the pathology of astrocytes and oligodendrocytes. Recent studies have shown the seeding capacity of GGT homogenates in vivo and in vitro [13,36,41]. However, little attention has been paid to the characteristics of tau deposits linked to the host tau.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study injected brain homogenates from subjects with sporadic AD, primary age-related tauopathy (PART), pure aging-related tau astrogliopathy (ARTAG), globular glial tauopathy (GGT), PSP, PiD, and frontotemporal lobar degeneration linked to P301L mutation (FTLD-P301L) into the ipsilateral corpus callosum of adult wildtype mice induced tau seeding of murine tau in the contralateral corpus callosum ( Ferrer et al, 2019 ). Phospho-tau deposits were found mainly in oligodendrocytes.…”
Section: Tau Uptake By Neurons Microglia and Astrocytesmentioning
confidence: 99%